KONSTITUSIONALITAS USIA CALON PRESIDEN DAN WAKIL PRESIDEN DALAM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 90/PUU-XXI/2023 - Fx. Valentino David Adison P; Bambang Arwanto (Cahaya Ilmu Bangsa, 2024)
This research aims to analyse the differences in qualifications for presidential candidates across various countries and to reconstruct how the Constitutional Court Decision Number 90/PUU-XXI/2023 could be determined. Consequently, it offers an objective perspective on the differing qualifications of presidential and vice-presidential candidates in various nations and provides guidelines for Indonesia. It seeks to present a legal and ethical viewpoint regarding the decision-making process of the Constitutional Court in relation to Decision Number 90/PUU-XXI/2023 and assess its connection to the ideal duties and authorities of the Constitutional Court. The issues discussed in this journal can be addressed by establishing a law that governs the age restrictions for presidential and vice-presidential candidates, which serves not only as guidance but also delineates the authority of the Constitutional Court.